2005
DOI: 10.1111/j.1365-2826.2005.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Neuroendocrine Response to Short‐Term Fasting in Rhesus Macaques

Abstract: When energy intake is restricted in mammals, there are neuroendocrine adjustments in the secretion of reproductive and metabolic hormones to reallocate energy for vital functions. In the present study, we investigated whether there were differences in the luteinising hormone (LH), growth hormone (GH) and cortisol responses to a 48-h fast in adult gonad-intact male and female rhesus macaques. In both male and female macaques, blood glucose levels were significantly lower in fasted than in control studies, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Sex steroids direct key regulatory mechanisms within the HPA axis of several mammalian species (ie, rat, 7684 mouse, 85 sheep, 86,87 monkey 88,89 and human 46,90–92 ). How gonadal steroids regulate ACTH and cortisol secretion is well articulated in the young adult rat, as highlighted in Fig.…”
Section: Experimental Insights Into and Clinical Inferences Regardingmentioning
confidence: 99%
“…Sex steroids direct key regulatory mechanisms within the HPA axis of several mammalian species (ie, rat, 7684 mouse, 85 sheep, 86,87 monkey 88,89 and human 46,90–92 ). How gonadal steroids regulate ACTH and cortisol secretion is well articulated in the young adult rat, as highlighted in Fig.…”
Section: Experimental Insights Into and Clinical Inferences Regardingmentioning
confidence: 99%
“…Whereas cortisol is relatively easy to measure because of its abundance in excreted samples, it exhibits a strong diurnal rhythm (Box 2), 5 is affected by awakening time, 37 and can change according to food intake. 38 These methodological issues exemplify a larger challenge in conducting behavioral endocrinology research. In some cases, the information we seek through the analysis of biological samples is yes or no: Has ovulation occurred?…”
Section: Which Comes First? the Hormone Or The Behavior? (Box 3)mentioning
confidence: 99%
“…Furthermore, research is inconsistent regarding the difference in the stress response between sex and or gender. Studies have shown mixed results regarding sex and gender responses to psychological stressors [14]- [17]. If sex alters the stress response then future studies assessing the effectiveness of a stress reduction technique would need to control for sex in the experimental design.…”
Section: Introductionmentioning
confidence: 99%